O professor iniciante da Educação Infantil de zero a três anos: desafios e perspectivas de atuação - Alves, Reiniane de Sousa Silva (2024)
This research aimed to understand how beginning teachers working at the Early Childhood Education Center with children from zero to three years old have faced the challenges that arise in their first years in this segment. In this qualitative study, data was collected through a questionnaire and semi-structured individual interviews with four early education beginning teachers from an Early Childhood Education Center directly managed by the Department of Education in the city of São Paulo. Theoretical framework was based on the studies of Marcelo García (1999) and Huberman (1992) concerning the early years of the teaching career, and on Abramowicz (2011); Fochi (2015), and Tardos & Szanto-Feder (2011) to support the discussion on Early Childhood Education. This distinction allowed for an understanding of the challenges and particularities of teaching in its initial stages. Data analysis was based on Prose Analysis (André, 1983) and enabled the development of five dimensions, covering the period of reception and support, monitoring, teaching practice with infants and young children, and context-based training, encompassing the feelings and difficulties experienced by the teachers at the beginning of their careers. This study revealed that teachers in Early Childhood Education with children from zero to three years old face various doubts, uncertainties, and challenges. The importance of providing support, reception, and monitoring in response to the needs of beginning teachers as they confront real-world experiences was noted. By promoting spaces for reflection, action, and knowledge sharing, the process of professional insertion in such a decisive segment for the future lives of infants and young children can be enhanced in terms of quality during the first stage of basic education, thereby contributing to the professional development of beginning teachers